Hyaluronic acid and vitamin E polyethylene glycol succinate functionalized gold-core silica shell nanorods for cancer targeted photothermal therapy - Jacinto, Telma A. (2020)
Gold-core mesoporous silica shell (AuMSS) nanorods unique physicochemical properties makes them versatile and promising nanomedicines for cancer photothermal therapy. Nevertheless, these nanomaterials present a reduced half-life in the blood and poor specificity towards the tumor tissue. Herein, d-α-Tocopherol polyethylene glycol 1000 succinate (TPGS) and Hyaluronic Acid (HA) were combined for the first time to improve the AuMSS nanorods biological performance. The obtained results revealed that AuMSS surface functionalization induced the surface charge neutralization, from -28 ± 10 mV to −3 ± 5 mV and −10 ± 4 mV for AuMSS-TPGS-HA (1:1) and (4:1) formulations, without impacting on nanomaterials’ photothermal capacity. Moreover, the AuMSS functionalization improved the nanomaterials hemocompatibility and selectivity towards the cancer cells, particularly in the AuMSS-TPGS-HA (4:1) formulation. Furthermore, both formulations were able to mediate an on-demand photothermal effect, that induced the HeLa cancer cells death, confirming its potential for being applied as targeted multifunctional theragnostic nanomedicines.